Pengaruh variasi besar butir dan variasi komposisi bahan terhadap kinerja briket arang tempurung kelapa dan sekam padi - Joniarta, I.W.; Wiratama, I.K.; Wijana, M.; Sujita, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
Abundant biomass waste is often thrown away. Careless disposal of waste will have a negative impact on environmental quality. Research regarding variations in composition and grain size of biomass waste charcoal briquettes on briquette performance is feasible. The aim of the research is to obtain briquettes that have high performance. The research method used was experimental research, coconut shell charcoal and rice husk charcoal, made in sizes 20 mesh, 60 mesh and 100 mesh. Then mixed with 15% starch adhesive with variations in the composition of coconut shell charcoal (TK): rice husk charcoal (SP), namely: I (75%:25%), II (50%:50%) and III (25%:75% ), After printing, the biket is dried in the sun and in the oven until it reaches a moisture content of (14-15)%. After the briquettes are dry, the heating value, flame duration and water boiling time are tested. In the calorific value test, the greater the composition (TK), the greater the calorific value produced. The highest heating value of 5937 kcal/kg was obtained from composition I, mesh 60 and the lowest heating value of 3714 kcal/kg was obtained from composition III mesh 60. The shortest flame duration of 1386.6 seconds occurred in mesh 20 composition III and the longest flame duration was 1933.2 seconds. obtained on mesh 100 composition I. In the Boilling Time test, it was found that the larger the grain size and the greater the composition of the coconut shell charcoal mixture in bioarang briquettes, the faster the water boiling time.